Teachers’ Questioning Behaviour and Instructional Organisation as Correlates of Students’ Achievement in English Language (2013)
The study investigated the relationship between teacher's questioning behaviour and instructional organization and students' achievement in English Language. The study adopted a descriptive research design. Four Research Questions were answered. The participants were 30 English Language teachers and 450 students randomly selected from 15 Senior Secondary Schools. The instruments for data collection were Teachers' Questioning Behaviour Observation Checklist (r = .79), Teachers' Instructional Organization Obs-ervation Rating Scale ( r = .81 ) and Achievement Test in English Language ( r = .78 ). Findings revealed that teachers ask display and referential questions that are largely mono-directional. There is a positive, very strong relationship between Teachers' Questioning Behaviour and students' achievement in English Language. Teachers' Instructional Organization has negative, very weak relationship with students' achievement in English Language.